Editorial. Processes of touristification and gentrification in Latin America and Spain: a panoramic view - Moriente , David; Botella Ordinas, Eva (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Editorial. Processes of touristification and gentrification in Latin America and Spain: a panoramic view